Influência de diferentes posturas sentadas e nível de controle de tronco no movimento de alcance em lactentes a termo e pré-termo tardios - Sato, Natália Tiemi da Silva (2017)
Aims: To identify the level of trunk control and to analyse the influence of sitting posture in a ring and seated with flexion at 90º in infants born late preterm infants with corrected age, and at term between 6 and 8 months with the support manual exact of trunk during reaching. Methods: A longitudinal study was performed with 36 full- term infants and 20 infants born preterm infants at 6-8 months of corrected age. The infants were submitted to three evaluations monthly: 1) Segmental Assessment of Trunk Control (SATCo), to identify the exact level of trunk control of infants; 2) assesssment of reaching movement, using kinematics; And 3) Alberta Infant Motor Scale (AIMS) to assess motor control of infants and to ensure the minimum 25th percentile for full-term infants. For the kinematic analysis, the infants were placed on a table in the sitting posture in a ring and seated with flexion at 90º of hip, knee and ankle. All infants during the reaching analysis received the exact and necessary manual support in the trunk according to the control level of each infant evaluated through the SATCo. To elicit reaching, an attractive, malleable or rigid object was presented on the midline, 45 ° to the right and 45 ° to the left of the infant's body. The total time of evaluation in each sitting posture was 2 minutes. It was considered variable full reaching frequency on the right, left and midline, and spatio-temporal variables to the right, left and midline (movement unit, straightness index, deceleration index, duration of movement, mean velocity, velocity peak, and trunk displacement. Results: Late preterm infants with corrected age were found to have lower trunk control compared to full-term infants at all ages evaluated. The level of trunk control presented a progressive and descending (cephalo-caudal) order with increasing age in both groups. The reaching frequency was greater at 6 months in the seated ring posture and at 7 and 8 months in the seated posture with 90 ° flexion in both groups. The sitting posture in a ring and with 90 ° flexion did not influence the kinematic variables, except for the right and midline velocity peak, and the trunk displacement to the right. On the other hand, significant differences between group and time were observed. The preterm group presented a higher number of movement units, lower, straightness index, higher average velocity and peak velocity, and lower trunk displacement in comparison to infants full term. In both groups, the spatio-temporal reaching variables improved over time, that is, older infants (8 months) presented lower number of movement units and higher straightness índex compared to younger infants (6 months). Conclusion: Late preterm infants had lower levels of trunk control compared to full-term infants. The postures seated in a ring and seated with 90 ° flexion did not influence the reaching behavior in the late term and preterm infants, since, the exact and necessary manual support was provided in the trunk of the infants, according to the level of control, evaluated through of SATCo. Thus, when the infant received the necessary manual trunk support, the different sitting postures did not influence the reaching behavior. Finally, preterm infants with corrected age, had less rectilinear, non-fluid and immature reaches compared to full-term infants at all ages evaluated. Reaches have become more mature over time, especially in full- erm infants.